The Ability to Manage Unexpected Events and the Vocational Identity in Young People: The Italian Validation of Planned Happenstance Career Inventory - Sica, Luigia Simona; Ponticorvo, Michela; Di Palma, Tiziana (Frontiers in Psychology, 2022)
The present study had two goals: to test the validity of Planned Happenstance Career Inventory (PHCI) in the Italian context and to explore the relations between PHC skills and vocational identity processes within a sample of 472 undergraduate students attending university in the southern of Italy. Moreover, we examined relations between the PHCI and measures of vocational identity processes. With regard to the first goal, results show that for the Italian version of the instrument was confirmed the multifactor structure of the original version. The multi-group analyses showed that invariance between genders is supported. Convergent validity and divergent validity of the measure were reported. Concerning the second goal, the skills of planned happenstance show different associations with Vocational Identity Dimensions. As hypothesized, the exploration and commitment dimensions of vocational identity status are positive related to Planned Happenstance Skills. These findings suggest implications for career guidance and counseling.